FREQUENCY OF CARIOUS PATHOLOGY AMONG THE POPULATION OF DIFFERENT CLIMATIC ZONES OF DAGESTAN REPUBLIC - O. R. Kurbanov; Z. O. Kurbanov; R. T. Magdiyev; D. M. Kudayev (Юг России: экология, развитие, 2015)
Aim. On a material of the survey of 1,963 representatives of the adult population we studied dental dis-ease rate. It revealed various levels of caries, the most common reasons for which are natural factors, primarily the natural fluoride content in the water. Methods. The reliability of the results and the representativeness of the sample were confirmed by modern methods of variation statistics. Results. High caries susceptibility rate determines the need of the adult population in all kinds of dental care. The data was obtained on the epidemiology of dental caries in the Republic of Dagestan, which showed significant differences of prevalence and intensity of the pathological process among the population of different climatic zones of the republic. It has been proved by the data on compara-bility of indexes of caries among adults living in different climatic zones of Dagestan Republic. Conclusion. It revealed various rates of caries diseases among the population, where the most common reasons are natural factors, primarily the natural fluoride content in the water.